Pengaruh Video Cerita Anak Terhadap Kemampuan Menyimak dan Berbicara Pada Anak TK Kecamatan Marpoyan Damai Kota Pekanbaru - Basori Basori (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2019)
This research is aimed to prove: (1) The influence of Children video story media on the student's language development in listening for kindergarten students of group A, (2) The influence of Children video story media on the student's language development in speaking for kindergarten students of group A, (3) The influence of Children video story media on the student's language development both listening and speaking for kindergarten students of group A. It uses quantitative Quasi Eksperimental research design with Nonequivalent Control Group Design. This research is conducted in both TK Al Mujahadah dan TK Sandhi Putra for the students of group A. The researcher collects data using the observation method and analyzed using statistic analysis of the Manova test SPSS vers 23 for windows. Based on the result of the research above, it can be concluded (The research findings show): (1) based on the Manova test, sig score = 0,000 which is far below 0,05. 0,000 < 0,05 means that the hypothesis about Children video story media toward listening for kindergarten students of group A can be received, (2) based on the Manova test, sig score = 0,000 that is far below 0,05. 0,000 < 0,05 means that hypothesis about Children video story media toward speaking for kindergarten students of group A can be received, (3) based on the Manova test, sig score = 0,000 that is far below 0,05. 0,000 < 0,05 means that hypothesis about Ipin and Upin video story media toward both listening and speaking for kindergarten students of group A can be received.